The Effect of Cognitive Behavioral Therapy on Self-Management and Self-Care Behaviors of Type 2 Diabetes Mellitus Patients - Purba, Jenny Marlindawani; Empraninta, Hanna Ester (Jurusan Keperawatan FIKES UNSOED, 2021)
Diabetes mellitus (DM) is the condition of metabolism affected by chronic hyperglycemia (the increase of glucose levels in the blood) caused by insulin secretion defect. One of the non-pharmacological therapies used to decrease the type 2 DM is cognitive behavioral therapy. The objective of the research was to identify the effect of Cognitive Behavior Therapy (CBT) on self management and self-care behaviors of type 2 DM patients. The research used a quasi-experimental method with a two-group pretest-posttest design. The samples were 70 respondents with 35 of them were in the intervention group and the other 35 were in the control group, taken by using a consecutive sampling technique. The data were gathered using the Diabetes Self-Management Questionnaires (DSMQ) and the Summary of Diabetes Self-Care Activities (SDSCA) questionnaires. The gathered data were analyzed by using paired t-test, and independent t-test. The results of the study showed that there were significantly differences of mean scores of self management and self care behaviors between intervention and control groupsÂ (t=13.24;Â p=0.00) and(t=14.63,p=0.00), respectively. It is recommended that cognitive behavior therapy can be used as one of the non-pharmacological therapiesto change self-care behaviors in type 2 DM patients.